A longitudinal study on the impact of perceived stress on academic engagement among deaf college students: the moderating effect of positive emotions - Chen, Tianlin; Xu, Kunjin; Luo, Lan; Chen, Yongfei (Frontiers in Psychology, 2024)
Introduction This longitudinal study sought to examine the dynamic influence of perceived stress on academic engagement among deaf college students, as well as assess the moderating role of positive emotions in this relationship. Given the unique challenges faced by deaf students in educational environments, understanding these dynamics becomes crucial for developing effective support strategies. Methods Across a seven-month period, encompassing two semesters, 223 deaf college students were evaluated three times using the Perceived Stress Questionnaire, the Academic Engagement Questionnaire, and the Positive Emotions Questionnaire. Results The results indicated that these students experienced high and variable levels of perceived stress, along with inadequate and similarly fluctuating levels of academic engagement. Their positive emotions were moderately low but relatively consistent. Perceived stress was found to be a negative predictor of academic engagement, while positive emotions positively predicted academic engagement. Furthermore, positive emotions acted as a moderating factor, alleviating the negative effects of perceived stress on academic engagement and serving as a protective mechanism for the academic engagement of deaf college students. Discussion This research sheds light on the impact of perceived stress on academic engagement in deaf college students, and reveals the underlying mechanisms, contributing precious empirical evidence to further our comprehension and enhance special education services.